The role of phronesis in Knowledge-Based Economy - Ceglarska, Anna; Cymbranowicz, Katarzyna (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2024)
The aim of this paper is to reflect on contemporary understanding of “knowledge” within the Knowledge-Based Economy. Since the pursuit of knowledge has been a longstanding focus of European culture since Greek philosophy, we employ the original ancient terminology. Applying the hermeneutics of ancient texts along with critical and comparative analysis can aid in differentiating between “knowledge” and “wisdom”, often linked in modern theories, while also connecting this issue to the Aristotelian concept of phronesis. The authors argue that since human relations impact social (and so—economic) spheres, the issue of phronesis, a relational type of knowledge, should not go unexamined. The idea that application of knowledge (rather than its mere acquisition), crucial for the Knowledge-Based Economy, was embedded in the Greek term oikonomiké, which provides a basis for considering oneself a phronimos. Our aim is to demonstrate the value of phronesis particularly in the fields of management and the philosophical foundations of economics, as the skills encompassed within it have the potential to aid in educating not only a “sage” but also an active member of the community, capable of acting in a manner that benefits both themselves and the society.